Total Quality Management sebagai Mekanisme Pendorong Competitive Advantagedan Inovasi untuk Mencapai Kinerja Perusahaan: Studi Empiris pada Perusahaan Real Estate - Ary Agus Setiawan; Fransiskus E. Daromes (Jurnal Bisnis dan Ekonomi, 2019)
Total Quality Management (TQM) is an effort so that the implementation of all company activities becomes integrated, planned, effective and efficient in order to produce good and sustainable performance. Total Quality Management (TQM) is also a guide for companies to be able to manage resources within the company to the maximum in order to improve their performance and be brave to compete with their competitors. This study investigates the effect of Total Quality Management (TQM) on Competitive Advantage, innovation and company performance. The research conducted through an online survey of property companies in Indonesia with research respondents was Middle-Top Level Management in the Indonesian property sector. Data analysis was carried out through a regression process and path analysis.The results of this study indicate that Total Quality Management (TQM) has a positive effect on Competitive Advantage, innovation but has no significant effect on company performance. Total Quality Management (TQM) affects the company's performance through the mechanism of innovation and Competitive Advantage